The Analysis of the Impact of GDP, FDI, Minimum Wage on Employment in Indonesia - Thomson Sitompul; Yansen Simangunsong (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2019)
Unlike the previous study in determinant of labor absorption, which focused on economic sector and took up regional scope, this paper examines the impact of Gross Domestic Product, Foreign Direct Investment and Minimum Wages on labor absorption in Indonesia which take the national scope and aggregate labor by using secondary series of time series data (1990-2015). This study contributes to the limited literature on aggregate employment and national scope as the impact of the minimum wage, GDP, FDI in developing countries, especially in Indonesia. By using multiple linear regression models, surprisingly, we find that GDP and Minimum Wages have a positive and significant impact to increase employment while FDI  does not affect employment in Indonesia.